Crystal structure of 5-(adamantan-1-yl)-3-[(4-trifluoromethylanilino)methyl]-2,3-dihydro-1,3,4-oxadiazole-2-thione, C20H22F3N3OS - Al-Wahaibi Lamya H.; Ghabbour Hazem A.; Al-Omary Fatmah A. M.; Tiekink Edward R. T.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C20H22F3N3OS, triclinic, P1 (no. 1), a = 6.9678(8) Å, b = 10.7614(14) Å, c = 13.0503(14) Å, α = 76.870(3)°, β = 88.004(4)°, γ = 87.275(4)°, V = 951.60(19) Å3, Z = 2, Rgt(F) = 0.0629, wRref(F2) = 0.1626, T = 100 K.